Potential of the adolescents, suffering from inflammatory bowel disease, for overcoming difficulties and achieving the intended goals - Wardak, Katarzyna; Celińska-Cedro, Danuta (Polish Journal of Public Health, 2015)
Introduction. Self-efficacy is one of the most important determinants of behavior of adults and adolescents. The degree of self confidence attributable to oneself in order to overcome the difficulties of life and to achieve one’s goals, both in healthy subjects and patients, determines the size of the effort and perseverance in taking action. According to The World Health Organization till 2020, chronic diseases will be the major cause of disability, and can be one of the most costly health problems. Therapy of chronic illness on the threshold of adult life requires, in addition to a comprehensive medical approach, the patient’s active participation in the implementation of the treatment process. Therefore, the potential of young people entering adult life with the burden of diagnosed disease may indicate the direction of education of the chronically ill adolescents. Aim. The aim of this study was to assess the potential of young people, both healthy and diagnosed with a chronic disease, to overcome difficulties of life. Material and methods. The study used a questionnaire and KompOs scale (Personal Competence Scale), a standardized test in the field of Health Psychology. The study included 80 subjects aged 15-18 years, 40 patients with inflammatory bowel disease treated in the IP-CZD in Warsaw and 40 healthy students from Rzeszow. The study used a questionnaire and KompOs scale (Personal Competence Scale), a standardized test in the field of Health Psychology. It allows the evaluation of such features in subjects such as strength and endurance needed to take action and then to continue it. Results. For young people despite of their health state the age of majority is mainly associated with a sense of autonomy, pursuing the job and the sense of responsibility for themselves and their families, without arousing fear in any of those groups. Parents of adolescents with IBD, however, still show too excessive protectiveness, and only 32.5% of children has a different view on that in comparison with 82.5% a group of healthy children.The sum of the results obtained on a scale KompOs, in both studied groups is at the same level of average values, (6 sten). The differences can be seen in correlation with sociodemographic characteristics such as: place of residence, financial situation or fertility families.Youth without chronic disease burden had the average level of self-efficacy (sten 6), whereas young patients diagnosed with IBD had a higher sense of efficacy (sten 7). Children with IBD, residing in large cities, have a higher average number of points in both the overall scale and subscales KompOs like (strength, endurance) than their healthy peers. Conclusions. Young people with non-specific inflammatory bowel disease have a greater sense of strength and perseverance than their peers. The statistical significance between the number of points was obtained in the KompOs scale in the city of >100 thousand. The financial situation of families is different in both groups, especially in the persistence subscale.